Music-search behaviour on a social Q&A site: A cross-gender comparison. (August 2020) - Deng, Shengli; Zhao, Anqi; Fu, Shaoxiong; Liu, Yong; Fan, Wenjie; Jiang, Yuting
While there have been numerous studies of music-search behaviour, little is known about gendered aspects of how it is carried out on social question and answer sites. The article examines gender differences manifested on one such site with regard to (a) the motivations of the person posing the question, (b) intervening variables that influence music-search behaviour and (c) the formulation of the questions. Results from manual categorisation and other analysis of 17, 380 music-relevant questions collected from the site show that males who asked questions did so more often, provided more answers and had more followers than female question-posters. Males tended to include music context information in questions asking for ready reference, whereas females often asked questions in a second-person pronoun aiming for promoting discussion. Such research results add to the current understanding of music-search behaviour and contribute new insights that can inform development of better music services/systems.